Pengaruh Fintech Payment, Lifestyle, dan Lingkungan Kampus terhadap Manajemen Keuangan Pribadi Mahasiswa Universitas Muhammadiyah Jember - Shafa Tamtowi Putri; Eko Budi Satoto; Ira Puspitadewi Samsuryaningrum (Universitas Nusantara PGRI Kediri, 2025)
Personal financial management is a systematic and structured approach to managing various aspects of personal finance. For students, personal financial management includes monitoring income and expenses related to basic needs, including education costs, transportation, food, and other basic needs. Using variables such as fintech payments, lifestyle, and the overall educational environment, this study will examine personal financial management at the University of Muhammadiyah Jember. Overall, 380 people were part of this quantitative study. To analyze the data, SPSS 28 was used along with multiple linear regression. The results of this study indicate that fintech payments, lifestyle and school environment each have a good and significant influence on the personal financial management of students at the University of Muhammadiyah Jember.